The trouble with footwear following stroke: a qualitative study of the views and experience of people with stroke. Issue 8 (9th April 2020) - Donovan-Hall, Margaret; Robison, Judy; Cole, Mark; Ashburn, Ann; Bowen, Catherine; Burnett, Malcolm; Mamode, Louis; Pickering, Ruth; Bader, Dan; Kunkel, Dorit
Abstract: Purpose: Foot problems and suboptimal footwear are risk factors for falls among the elderly. Footwear choice may, therefore, be important for people with balance impairment following stroke, but little is known about their experience. This study explored foot problems experienced following stroke, factors influencing footwear choices and views of footwear in use. Methods: Semi-structured interviews with 15 people with stroke, purposively sampled from respondents to a screening survey. Results: Participants typically experienced impaired mobility with balance problems and felt at risk of falling. Stroke related foot problems, including altered sensation, edema, and foot drop, predominantly on the stroke affected side, influenced footwear priorities. Footwear choices prioritized comfort, security, and convenience, sometimes in tension with concern about appearance. Challenges included choosing appropriate indoor footwear and finding shoes to accommodate their orthoses and edema. Participants highlighted perceived lack of footwear advice from health care professionals and variable experience of shoe shopping. Conclusions: Foot problems, as well as gait and balance impairment, have implications for footwear priorities following stroke, but people felt unsupported in making healthy footwear choices. Health care professionals could be trained to routinely deliver footwear assessment and advice and facilitate referrals to podiatrist, when appropriate. Implications for rehabilitation: Foot problems, as well as gait and balance impairment, have implications for footwear priorities following stroke. People with stroke perceive a lack of professional advice about footwear and feel unsupported making healthy footwear choices. Health care professionals could be trained to routinely deliver an initial footwear assessment and advice as part of stroke rehabilitation. A greater transparency and knowledge of referral pathways into podiatry services for Health care professionals and patients would give access to specialist advice where appropriate.